Mentha arvensis (Linn.)-mediated green silver nanoparticles trigger caspase 9-dependent cell death in MCF7 and MDA-MB-231 cells - Banerjee PP (Dove Medical Press, 2017)
Prajna Paramita Banerjee,1 Arindam Bandyopadhyay,1 Singapura Nagesh Harsha,2 Rudragoud S Policegoudra,3 Shelley Bhattacharya,4 Niranjan Karak,2 Ansuman Chattopadhyay1 1Molecular Genetics Laboratory, Department of Zoology, Visva-Bharati, Santiniketan, West Bengal, 2Advanced Polymer and Nanomaterial Laboratory, Department of Chemical Sciences, Center for Polymer Science and Technology, Tezpur University, Napaam, 3Division of Pharmaceutical Technology, Defence Research Laboratory, Tezpur, Assam, 4Environmental Toxicology Laboratory, Department of Zoology, Visva-Bharati, Santiniketan, West Bengal, India Introduction: Leaf extract of Mentha arvensis or mint plant was used as reducing agent for the synthesis of green silver nanoparticles (GSNPs) as a cost-effective, eco-friendly process compared to that of chemical synthesis. The existence of nanoparticles was characterized by ultraviolet–visible spectrophotometry, dynamic light scattering, Fourier transform infrared spectroscopy, X-ray diffraction, energy-dispersive X-ray analysis, atomic-force microscopy and transmission electron microscopy analyses, which ascertained the formation of spherical GSNPs with a size range of 3–9 nm. Anticancer activities against breast cancer cell lines (MCF7 and MDA-MB-231) were studied and compared with those of chemically synthesized (sodium borohydride [NaBH4]-mediated) silver nanoparticles (CSNPs). Materials and methods: Cell survival of nanoparticle-treated and untreated cells was studied by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. Cell-cycle analyses were carried out using fluorescence-activated cell sorting. Cell morphology was observed by fluorescence microscopy. Expression patterns of PARP1, P53, P21, Bcl2, Bax and cleaved caspase 9 as well as caspase 3 proteins in treated and untreated MCF7 and MDA-MB-231 cells were studied by Western blot method. Results: MTT assay results showed that Mentha arvensis-mediated GSNPs exhibited significant cytotoxicity toward breast cancer cells (MCF7 and MDA-MB-231), which were at par with that of CSNPs. Cell cycle analyses of MCF7 cells revealed a significant increase in sub-G1 cell population, indicating cytotoxicity of GSNPs. On the other hand, human peripheral blood lymphocytes showed significantly less cytotoxicity compared with MCF7 and MDA-MB-231 cells when treated with the same dose. Expression patterns of proteins suggested that GSNPs triggered caspase 9-dependent cell death in both cell lines. The Ames test showed that GSNPs were nonmutagenic in nature. Conclusion: GSNPs synthesized using Mentha arvensis may be considered as a promising anticancer agent in breast cancer therapy. They are less toxic and nonmutagenic and mediate caspase 9-dependent apoptosis in MCF7 and MDA-MB-231 cells. Keywords: nanoparticles, EDX, TEM, breast cancer cells, anticancer, nonmutagenic